PENINGKATAN KETERAMPILAN BERCERITA MELALUI MEDIA WAYANG SUKURAGA BERBASIS 5 KARAKTER DI KELAS TINGGI - Juliana, Asha Dena; Nurasiah, Iis; Eska Wardana , Aditia (ATTA`DIB, 2019)
The research aims to improve storytelling skills through the media of sukuraga’spuppetbased on 5 characters in high class SDN SelabintanaWetan. The type of this research is Classroom Action Research (CAR) using the Kemmis and Mc.Taggart cycle design models.The subjects of the research were the fifth grade students at SDN SelabintanaWetan with a total of 22 students.The study was conducted in two cycles completed with data collection in the form of interviews, observation sheets, test results, documentation results and field notes.The results of the studentspretest research who obtained classical completeness 18%or a total of 4 students achieving the KKM value and 82% or 18 students who have not yet achieved the KKM value, in cycle I who received classical mastery as much as 77% or a total of 17 students and 23% or 5 students who had not yet achieved the KKM score and in cycle II obtained classical completeness 95% or 21 students and 5% or 1 student who had not yet reached KKM.The conclusion of this study is that the use of sukuraga’spuppetmediabased on 5 character can improve the storytelling skills of students in fifthgrade at SDN SelabintanaWetan in the 2019-2020 school year.